Estrutura e dinâmica da comunidade de ciliados (Protozoa, Ciliophora) associada aos fitotelmos da bromélia Aechmea distichantha Lem. - Buosi, Paulo Roberto Bressan (2011)
The aims of this study were to investigate the influence of the precipitation volume over the abundance, species richness and community structure of the ciliate community associated with the tanks of the bromeliad Aechmea distichantha Lem., in a riparian vegetation of the Paraná River. It was intended, yet, to verify if the size of the tanks and the water volume accumulated in each one of those influences the attributes (species richness and abundance) of the ciliate community, and also if plants that are geographically closer have similarity in the species composition and in the structure of the ciliate community. The study was conducted at the left border of the Paraná River, which is characterized by the presence of several rocky walls that allow the establishment of populations of epiphytic plants. The samplings were performed in the year of 2010, with three samplings in the dry season and three in the rainy season, in three layers of the rock walls (lower, middle, and upper). A total of 72 samples were taken (four individuals in each layer) in both periods. The values of species richness ranged from two to 20 species in the dry season and from six to 25 species in the rainy season, which presented values significantly higher than the dry season, whereas the differences between the layers did not present values significantly distinct. Regarding the species abundance, it were recorded average values from 0,04 to 238 ind.mL-1 in the dry season and from 0,02 to 477 ind.mL-1 in the rainy season. An Analysis of Variance (ANOVA) showed that the values of species abundance did not differ significantly for both season and layers. An Detrended Correspondence Analysis (DCA) evidenced that the structure of the ciliate community changed substantially due to the rainfall. On the other hand, simple regression analysis evidenced only a reverse relation between individual densities and water volume, and none relation neither between this variable with the species richness nor between the sizes of the tanks with the community attributes. In the same way, the Mantel's tests showed that there was no spatial structuring neither in species composition nor in the structure of the ciliate community associated with the tanks of the bromeliad A. distichantha.